DESENVOLVIMENTO TECNOLÓGICO, CARACTERIZAÇÃO E AVALIAÇÃO DE CIMENTO DE IONÔMERO DE VIDRO CONTENDO MICROPARTÍCULAS INOVADORAS DE DIGLUCONATO DE CLOREXIDINA - Reinke, Stella Maria Glaci (2014)
Glass ionomer cement (GIC) is a widely used material in dentistry for providing both adhesion to dental tissues and anticariogenic activity. Previous studies have suggested that the incorporation of antimicrobials to GIC allows an increase in the longevity of restorations as well as an antibacterial activity against biofilm deposited on the restorations. In order to have a better incorporation of an antimicrobial to GIC, this study aims at evaluating a GIC containing chlorhexidine digluconate (Clx Dg)-loaded (meth)acrylic microparticles. In brief, it was carried out a laboratory study (1) to formulate and to evaluate Clx Dg-loaded (meth)acrylic microparticles for being added into a commercial GIC and (2) to investigate the cytotoxic and mechanical properties of this novel material. Microparticles were obtained by the non-aqueous emulsion/solvent evaporation method using Eudragit® S100 and RS100 as polymers and Clx Dg at 10 and 25%. The characterization was performed by morphological, thermal and spectroscopic methods and by evaluating the drug content and drug release. The two best formulations of microparticles were incorporated into a commercial GIC and resulted in two new experimental materials. The pure GIC was used as control. The biocompatibility of these materials was investigated using dental pulp cells and human gingival fibroblasts. In addition, the antimicrobial activity and the mechanical properties (resistance to abrasion, compressive strength, diametral tensile strength and flexural strength) were carried out. Clx Dg-loaded (meth)acrylic microparticles were successfully prepared. Micrometer-sized, heat-stable, and amorphous/non-crystalline formulations with high drug-loading efficiencies, effective antimicrobial activity, and a controlled release of the drug were obtained. The incorporation of Clx Dg-loaded (meth)acrylic microparticles into GIC provided antimicrobial properties to this material and did not increase its cytotoxicity. The mechanical properties demonstrated positive and negative changes after the microparticles incorporation. However these changes did not contraindicate the use of this new material. It was concluded that it was possible to obtain a GIC containing innovative Clx Dg-loaded (meth)acrylic microparticles that showed suitable features and performance. This new material has a promising potential for restorative procedures. However, additional clinical studies are required.